Some Aspects of Institutional Agricultural Credit on Agricultural Production A Case Study in The Vavuniya District - Umashankar, K.; Jogaratnam, T.; Sivarajasingam, S. (Jaffna Science Association, 2000)
Credit is thought to be a strategic variable in enhancing agricultural production in developing countries. It is in this backdrop, that an attempt is made to understand the dynamics of the agricultural credit system in Vavuniya district, where the traditional paddy based agricultural system is in the phase transition into a commercialized agricultural system. Vavuniya district is considered to be a relatively less endowed district in Sri Lanka. It is a district with typical dry zone characteristics. This study was carried out to asses the credit need of the red onion cultivators, contribution percentage of the non-institutional sources as against the institutional sources and the factors affects the farmers access to the credit. Final objective is to recommend possible measures to evolve a better credit culture in the district. Purposive randomly selected sample farmers from the Kovilkulam and Pampamadu agrarian service center divisions were interviewed with a structured questionnaire to obtain the information. Descriptive statistics, chi-square test, and simple tabular analysis were used to analyze the data. Credit needs of the farmers were estimated on the basis of potential credit need, expressed credit need and credit need based on the 75 per cent of the total cash cost of production. Assessment of the credit need based on the cost of cultivation showed a highest value than other two. Expressed credit need of the farmers was found to be far below than the credit need estimated based on the cost of cultivation. But potential credit need of the farmers showed the lowest value. Out of the total borrowing of the red onion cultivators in the Vavuniya Divisional secretariat division, informal sources contributed 31 percent as against the formal sources. But total Bank loans alone contributed 42.25 percent out of the total borrowing of the farmers. This study identified several factors such as age, educational level, family labour previous borrowing experience, availability of water and storage facilities, size of holdings and off farm income which have been influencing farmers effective access to the institutional credit. Finally the research recommend some possible measures to evolve better credit culture to improve the productivity of farmers through proper supervision and guidance of borrowers and by ensuring timely provision to adequate amounts of formal credit. Replacing the asset based lending system by introducing a group based lending scheme, allowing farmers organization to be as a guarantor to the poor farmers, channeling more credit to the construction of storage structures and rehabilitation of the wells, extending the Bank services via introducing the temporary mobile service units during the lending seasons, employing more clerical staff to reduce the paper works of the borrowers and reducing the time to sanction the loans. could be expected to prevent farmers from securing loans from high cost informal sources.